TRANSFORMATION OF WESTERN PODILLIA TRADITIONAL DANCE IN THE CONTEXT OF REGIONAL FESTIVAL MOVEMENT - Liudmyla Shchur; Bohdan Vodianyi; Valentyna Vodiana (International Journal of Innovative Technologies in Social Science, 2021)
The article covers the issue of transformation of traditional dance in the context of festival movement in the particular region and Ukraine as a whole. The research article analyses the functioning of art folklore festivals on the territory of Western Podillia. The study investigates the organization of art festivals of the region in historical and chronological perspective and presents the key tasks for their holding. The article partially covers the activities of some dance and folk-ritual groups of Western Podillia, which are active participants and popularisers of folk art, in particular of local traditional dances. The study reveals the issues related to the functioning and development of traditional dance in terms of folklorism, which is implemented during the «Ternopil talismans», regional festival of folk crafts, folklore and choreography, which hosts the «Ternopil Polka», festival of authentic dance (Ternopil); «Red guilder-rose», folk dance festival (Ternopil); «Bells of Lemko region», All-Ukrainian festival of Lemko culture (Bychova tract of Monastyryskyi district); «Embroidery blossoms in Borshchiv region», annual All-Ukrainian Folklore and Art Festival (Borshchiv) and other local festivals. The article highlights the importance of organizing and holding regional local holidays and folklore and art festivals in the context of the revival of the national and cultural identity of Western Podillia as an integral part of Ukraine.